ИННОВАЦИОННАЯ ПОЛИТИКА В СЕЛЬСКОМ ХОЗЯЙСТВЕ: НАПРАВЛЕНИЯ И МЕХАНИЗМЫ - M. P. Khagurova (Новые технологии, 2018)
The article considers competitiveness of domestic agricultural technologies, the specific weight of agricultural producers of different forms of production organization. The main reasons for the low level of innovative technologies are determined and an approximate scheme for the development of the forecast and programs for the scientific and technological development of agriculture is proposed.